2012
DOI: 10.1128/aac.05642-11
|View full text |Cite
|
Sign up to set email alerts
|

Nonthermal Atmospheric Plasma Rapidly Disinfects Multidrug-Resistant Microbes by Inducing Cell Surface Damage

Abstract: Plasma, a unique state of matter with properties similar to those of ionized gas, is an effective biological disinfectant. However, the mechanism through which nonthermal or "cold" plasma inactivates microbes on surfaces is poorly understood, due in part to challenges associated with processing and analyzing live cells on surfaces rather than in aqueous solution. Here, we employ membrane adsorption techniques to visualize the cellular effects of plasma on representative clinical isolates of drug-resistant micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(119 citation statements)
references
References 29 publications
4
114
0
1
Order By: Relevance
“…Independent of our work, Joshi et al reached similar conclusions [13]. A large number of papers followed [31][32][33]. In this sense, biofilms represent an even more challenging task because bacteria are shielded by the polymeric matrix.…”
Section: Introductionsupporting
confidence: 52%
“…Independent of our work, Joshi et al reached similar conclusions [13]. A large number of papers followed [31][32][33]. In this sense, biofilms represent an even more challenging task because bacteria are shielded by the polymeric matrix.…”
Section: Introductionsupporting
confidence: 52%
“…The result of the present study showed that generally, the MIC value of bacteria exposed to (+)- Evidently exposure to (+)-1,1'-bislunatin caused an obvious change in the permeability of bacterial cell membrane and degeneration of cell membrane. According to Kvam et al (2012) the cell poration and lysis are believed to be indicators of gradual cellular protein and nucleic acid leakage from the cell. The observation on cellular morphology showed that the bacteria cells deflated after treatment with (+)-1,1'-bislunatin, causing losses of cell wall function as protector or barrier between organs and cellular fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Examples reported of CAP capability for decontaminating multidrug resistant bacteria including the highly resistant MRSA [109][110][111] and Pseudomonas aeruginosa. [110] Notably, CAP is also effective on the sterilization resistant Deinococcus radiodurans bacteria.…”
Section: Mechanisms Of Microbial Inactivation By Capmentioning
confidence: 99%
“…Examples reported of CAP capability for decontaminating multidrug resistant bacteria including the highly resistant MRSA [109][110][111] and Pseudomonas aeruginosa. [110] Notably, CAP is also effective on the sterilization resistant Deinococcus radiodurans bacteria. [112] Less resistant vegetative bacteria have also been tested against the antimicrobial activity of CAP, and were eliminated with different degrees of survival, including gramnegative: Escherichia coli [111,113,114] , Salmonella typhimuriu [115] , and gram-positive Staphylocuccus epidermidis [90,113,116] , Staphylococcus aureus [90,114] , Micrococcus luteus [95] , Streptococcus pyogenes [90] , Enterococcus faecalis [117] and Enterococcus faecium.…”
Section: Mechanisms Of Microbial Inactivation By Capmentioning
confidence: 99%